UPAH PANEN PEKERJA TANI SAWAH (Analisis Sosiologi Gender Tentang Perbedaan Upah Antar Pekerja Perempuan dengan Pekerja Laki-laki dari Jenis Pekerjaan yang Sama di Nagari Riak Danau, Kecamatan Basa Ampek Balai Tapan, Kabupaten Pesisir Selatan) - Utari, Riska - (Pendidikan Sosiologi, 2014)
Workers women and men doing the same work the rice fields, the rice harvest, with the same time, in the same location and the same job but getting different pay. Therefore the formulation of the problem, namely "whether the factors that cause the difference in wages to workers harvesting paddy peasant women and men in Nagari Ripple Lake". The theory used in this research is a social act by Max Weber, which is in the form of social action: instrumental rational action, and traditional measures, in addition to the theory proposed by Schopenhaur Nature and nuture expressed by John Stuart Mill is also used to support the theory of action the social. Based on the results of research conducted, the factors that cause the wages of women and men is caused by (a) the experience factor (hereditary), previous experience makes landlady impose different wages, because it has been so from the former. (b) factors of the attitude of the women who did not refuse or just receive different wages. (c) factors of the notion of men are stronger than women. (d) by a factor of dependents living men.